Genomic Epidemiology of Penicillin-Nonsusceptible Pneumococci with Nonvaccine Serotypes Causing Invasive Disease in the United States - Andam, Cheryl P. (J Clin Microbiol, 2017)
Conjugate vaccination against seven pneumococcal serotypes (PCV7) reduced disease prevalence due to antibiotic-resistant strains throughout the 2000s. However, diseases caused by resistant nonvaccine type (NVT) strains increased. Some of these emerging strains were derived from vaccine types (VT) that had changed their capsule by recombination. The introduction of a vaccine targeting 13 serotypes (PCV13) in 2010 has led to concern that this scenario will repeat itself. We generated high-quality draft genomes from 265 isolates of NVT pneumococci not susceptible to penicillin (PNSP) in 2009 and compared them with the genomes of 581 isolates from 2012 to 2013 collected by the Active Bacterial Core surveillance (ABCs) of the Centers for Disease Control and Prevention (CDC). Of the seven sequence clusters (SCs) identified, three SCs fell into a single lineage associated with serogroup 23, which had an origin in 1908 as dated by coalescent analysis and included isolates with a divergent 23B capsule locus. Three other SCs represented relatively deep-branching lineages associated with serotypes 35B, 15A, and 15BC. In all cases, the resistant clones originated prior to 2010, indicating that PNSP are at present dominated by descendants of NVT clones present before vaccination. With one exception (15BC/ST3280), these SCs were related to clones identified by the Pneumococcal Molecular Epidemiology Network (PMEN). We conclude that postvaccine diversity in NVT PNSP between 2009 and 2013 was driven mainly by the persistence of preexisting strains rather than through de novo adaptation, with few cases of serotype switching. Future surveillance is essential for documenting the long-term dynamics and resistance of NVT PNSP.